Sustainable removal of pernicious arsenic and cadmium by a novel composite of MnO2 impregnated alginate beads: A cost-effective approach for wastewater treatment - Shim, Jaehong; Kumar, Manish; Mukherjee, Santanu; Goswami, Ritusmita (Journal of environmental management, 2019)
There is a dire necessity of developing low cost waste water treatment systems, for the efficient removal of noxious heavy metals (and metalloids) such as Arsenic (As) and Cadmium (Cd). Magnetic biopolymer (CABs-MO) was synthesized by the entrapment of nanocrystalline MnO2 in the polymeric microcapsules of calcium alginate (CABs). Batch experiments were conducted under constant pH (6.5), temperature (25OC), different initial concentrations (30–300 mg L−1) and contact times (0–48 h) to study the adsorption isotherms and removal kinetics of pristine (CABs) and hybrid biopolymer (CABs-MO) for the removal of As and Cd. The pseudo-equilibrium process was mathematically well explained by the pseudo-second-order kinetic (R2 ≥ 0.99) and Langmuir isotherm model (R2 ≥ 0.99) with the highest monolayer sorption capacity of 63.6 mg g−1 for Cd on CABs-MO. The As removal rate was maximum up to 6.5 mg g−1 after 12 h of contact period in a single contaminant system than in the mixed contaminant (As + Cd) system (0.8 mg g−1), though the effect was non-significant for Cd (p < 0.05; t-test). The performance of the 10 mM HCl as a regenerating agent was superior (for As in comparison to Cd, p < 0.05; t-test) compared to distilled water (DW) through three to five regeneration cycles. Therefore, the obtained results clearly validate the feasibility of CABs-MO as a potential promising adsorbent for removing metal contaminants from the wastewater. Further research is required to study the decontamination of emerging contaminants with such novel composite beads characterized by varied physico-chemical properties. [Display omitted] •Calcium alginate (CABs) and MnO2 (MO) were hybridized for the synthesis of CABs -MO.•The BET surface area of CABs-MO was of two orders of magnitude higher than CABs.•The removal of As (∼8X) and Cd (∼2X) was high in single contaminant system.•Maximum Langmuir monolayer sorption capacity was observed for Cd (63.6 mg g−1).•HCl showed better performance than water as a desorption agent upto five cycles.